Penerapan Pijat Oksitosin Terhadap Produksi ASI di Ruang Cempaka RSUD Dr.Soehadi Pridjonegoro Sragen - Fildzah Shella Afriany; Anjar Nurrohmah; Neny Utami (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Background: Breast Milk (ASI) is a fatty emulsion in lactose protein and inorganic salts secreted by the mother's mammary gland, useful as food for infants. Breast milk is difficult to achieve because one of them is breast milk that does not come out or does not run smoothly. One of the non-pharmacological arrangements to help smooth the release of breast milk can be done by oxytocin massage. Objective: Knowing the results of the implementation of oxytocin massage to breast milk production at the Cempaka Ward of dr. Soehadi Pridjonegoro Sragen Hospital. Method: This study is a descriptive study in the form of a case study conducted on 2 postpartum mother respondents by massage oxytocin for 2 consecutive days with a frequency of 2x a day for 10-15 minutes. Result: The study of oxytocin massage in both postpartum mothers on the first day has not changed breast milk production. Then on the second day of breast milk production, the two respondents showed an increase, evidenced by the increase in breast milk, empty breasts after catching up, and the breasts looked full before breastfeeding. Conclusion: There is an increase in breast milk production before and after giving oxytocin massage to postpartum mothers in the Cempaka Room of dr. Soehadi Prjonegoro Sragen Hospital.